2022
DOI: 10.4018/978-1-6684-3380-5.ch001
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Network Analysis (SLNA) Towards Corporate Sustainability in the Context of Triple Bottom Line

Abstract: Sustainability basically means to continue, to maintain anything. The equivalent of sustainability on a firm basis is expressed as corporate sustainability. Corporate sustainability has three dimensions: economic, social, and environmental. This study aimed to use the systematic literature network analysis (SLNA) method to evaluate corporate sustainability on triple bottom line (TBL). In this context, SLNA on the development and evolution of the corporate sustainability issue was carried out with 1929 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…Given that four authors are ranked according to both citation and co-citation rankings (Shamir, van Knippenberg, Kantabutra and Mumford), these four scholars have the highest impact within the organizational vision knowledge domain. Similar to the journal citation and co-citation analysis results, these authors are not well-identified in the sustainability sphere [49][50][51][52][53][54][55], except Kantabutra, who has continuously been identified by different scholars as a top scholar in the sustainability literature [20,46,[56][57][58].…”
Section: Author Citation and Co-citation Analysessupporting
confidence: 60%
See 4 more Smart Citations
“…Given that four authors are ranked according to both citation and co-citation rankings (Shamir, van Knippenberg, Kantabutra and Mumford), these four scholars have the highest impact within the organizational vision knowledge domain. Similar to the journal citation and co-citation analysis results, these authors are not well-identified in the sustainability sphere [49][50][51][52][53][54][55], except Kantabutra, who has continuously been identified by different scholars as a top scholar in the sustainability literature [20,46,[56][57][58].…”
Section: Author Citation and Co-citation Analysessupporting
confidence: 60%
“…Sustainability 2023, 15, x FOR PEER REVIEW 9 of 28 results, these authors are not well-identified in the sustainability sphere [49][50][51][52][53][54][55], except Kantabutra, who has continuously been identified by different scholars as a top scholar in the sustainability literature [20,46,[56][57][58].…”
Section: Author Citation and Co-citation Analysesmentioning
confidence: 99%
See 3 more Smart Citations